2022
DOI: 10.1002/jcph.1966
|View full text |Cite
|
Sign up to set email alerts
|

Dosing Regimen Prediction and Confirmation With Rivaroxaban for Thromboprophylaxis in Children After the Fontan Procedure: Insights From the Phase III UNIVERSE Study

Abstract: Thrombosis remains an important complication for children with single-ventricle physiology following the Fontan procedure, and effective thromboprophylaxis is an important unmet medical need. To obviate conventional dose-finding studies and expedite clinical development, a rivaroxaban dose regimen for this indication was determined using a model-informed drug development approach. A physiologically based pharmacokinetic rivaroxaban model was used to predict a pediatric dosing regimen that would produce drug ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…for the prevention of thromboembolic events after major orthopedic surgery, applying a regimen of two times a day in children 9,20 . The UNIVERSE study confirmed that the body weight–adjusted dose regimen in post‐Fontan patients between 2 and 8 years of age resulted in rivaroxaban exposure that matched the adult reference exposures at 10 mg o.d 20 . The post‐Fontan patients who received rivaroxaban had a similar safety profile and fewer thrombotic events, albeit not statistically significant, compared with those in the ASA group 21 .…”
Section: Introductionmentioning
confidence: 69%
See 4 more Smart Citations
“…for the prevention of thromboembolic events after major orthopedic surgery, applying a regimen of two times a day in children 9,20 . The UNIVERSE study confirmed that the body weight–adjusted dose regimen in post‐Fontan patients between 2 and 8 years of age resulted in rivaroxaban exposure that matched the adult reference exposures at 10 mg o.d 20 . The post‐Fontan patients who received rivaroxaban had a similar safety profile and fewer thrombotic events, albeit not statistically significant, compared with those in the ASA group 21 .…”
Section: Introductionmentioning
confidence: 69%
“…The bridging approach made use of (i) available dose-exposure data of rivaroxaban from another pediatric program, EINSTEIN-Jr, which investigated rivaroxaban for the treatment of acute VTE in children between 0 and 18 years of age [1][2][3][4][5] and (ii) preexisting PBPK and popPK models of rivaroxaban in pediatric patients. [6][7][8]20 At first, the predictive performances of the Fontan-PBPK model 20 and the EINSTEIN-Jr popPK model 8 for the UNIVERSE data were retrospectively assessed. Both models showed a tendency toward S1).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations